Conselho Municipal de Educação de Ponta Grossa: aspectos históricos, funções e contribuições - Oliveira, Izolde Hilgemberg de (2008)
This research aims at analyzing the trajectory, structure and functioning of the Municipal Council of Education of Ponta Grossa City – Paraná State – Brazil, as well as investigating the extent to which this Council has been a tool for democratization in educational decision-making. The theoretical framework is based on authors who discuss the concepts of democracy and representative democracy, as well as the concepts of State and civil society (Bobbio, Held, Chauí, Carnoy and Gramsci, among others). The fieldwork comprises the following strategies of data collection: documentary analysis (laws, internal rules of the Council, meeting reports, official documents approved by the Council); non-participatory observations of the Council’s meetings; an interview with the town councilor who proposed the creation of the Municipal Council of Education; and interviews with 16 other councilors. The main findings are as follows: (a) although the Council investigated can be considered as an important means for the participation of civil society in education management, this Council has been legitimizing education policies formulated by the Municipal Secretariat of Education, rather than acting as a source of new proposals and their implementation; and (b) the contributions of the Municipal Council of Education of Ponta Grossa to the democratization of educational decision-making have, so far, been weak – and less than might have been expected. These conclusions must be understood in context, involving a range of factors (mediations), such as: the period of the Council’s existence; the conservative features of local society; the few opportunities for effective democratic and participatory experiments; the power relations inside the Municipal Secretariat of Education; the lack of councilor training; and the features of the process of democratic construction in Brazilian society.